Gambaran Tingkat Kepuasan Pasangan Usia Subur Terhadap Pelayanan Metode Kontrasepsi Jangka Panjang - Kekado, Miranda Nitani; Armini, Ni Wayan; Suarniti, Ni Wayan (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Satisfaction is the level of someone's feelings after comparing performance with expectations. The use of long-term contraceptive methods by couples of childbearing age at Community Health Center I Area of the East Denpasar is still low, namely not yet reaching the target of 55%. This study aims to identify the level of satisfaction of couples of childbearing age regarding the dimensions of reliability, responsiveness, physical evidence, assurance of certainty and empathy with Long-Term Contraceptive Method services. Data collection was carried out in March-April 2024. Data analysis uses descriptive analysis, Customer Satisfaction Index and Cartesian Importance Performance Analysis Diagram. This research used a cross sectional approach with a purposive sampling technique for a population of 4,766 people, with a total sample of 108 couples of childbearing age. The research results show that couples of childbearing age are satisfied (85.25%) and have good performance, the average level of conformity between reality and expectations of the five dimensions of service quality is very similar (93.91%) to what was expected, but there is still a difference The reality score and expectation value are (-0.28), thus the main priority that must be implemented or improved is that service staff need to provide comprehensive communication, information and education, staff are willing to listen to patient complaints, reasonable costs or affordable rates and availability. service policy according to the type of service offered. It is recommended that Community Health Centers need to evaluate and improve performance, provide reasonable costs and provide policies according to the type of services provided.